110k views
1 vote
6^{\frac{2}{x}}+4^{\frac{1}{x}}=\frac{10}{3}\cdot 12^{\frac{1}{x}}`

User Maritess
by
4.4k points

2 Answers

4 votes

This is the right answer and how!

~!HOPE IT HELPS!~

6^{\frac{2}{x}}+4^{\frac{1}{x}}=\frac{10}{3}\cdot 12^{\frac{1}{x}}`-example-1
User Return True
by
4.8k points
1 vote

Answer:

x = 1

x = -1

Explanation:

Solve the equation


6^{(2)/(x)}+4^{(1)/(x)}=(10)/(3)\cdot 12^{(1)/(x)}

First, note that


4^{(1)/(x)}=2^{(2)/(x)}

Now, divide the whole equation by
2^{(2)/(x)}


\frac{6^{(2)/(x)}}{2^{(2)/(x)}}+\frac{2^{(2)/(x)}}{2^{(2)/(x)}}=(10)/(3)\cdot \frac{12^{(1)/(x)}}{2^{(2)/(x)}}


3^{(2)/(x)}+1=(10)/(3)\cdot \frac{12^{(1)/(x)}}{4^{(1)/(x)}}\\ \\3^{(2)/(x)}+1=(10)/(3)\cdot 3^{(1)/(x)}

Use substitution


t=3^{(1)/(x)}

Then


t^2+1=(10)/(3)t

Multiply by 3:


3t^2+3=10t\\ \\3t^2-10t+3=0\\ \\D=(-10)^2-4\cdot 3\cdot 3=100-36=64\\ \\t_(1,2)=(-(-10)\pm √(64))/(2\cdot 3)=(10\pm 8)/(6)=3,(1)/(3)

Thus,


3^{(1)/(x)}=3\Rightarrow (1)/(x)=1,\ x=1\\ \\3^{(1)/(x)}=(1)/(3)\Rightarrow (1)/(x)=-1,\ x=-1

User Independent
by
5.6k points